Suitability of Roselle-Hibiscus sabdariffa L. as Raw Material for Soft Drink Production - Serifat Olatundun Salami; Anthony Jide Afolayan (Journal of Food Quality)
Consumption of conventional soft drinks has been linked with several diseases in man. This has called for the consumption of natural soft drinks such as roselle drink. Roselle-Hibiscus sabdariffa L. is the major raw material for the production of beverage called cranberry (Florida), bissap (Egypt), zobo (Nigeria), and roselle drink generally. The nutritional and phytochemical properties found in roselle make the plant useful in the preparation of some drugs and food. It has been reported that consumption of roselle drink helps to cure diseases such as high blood pressure and diabetes. The pharmacological properties of the plant are traceable to activities of flavonoid and anthocyanin which are the major antioxidants in roselle. Good aroma and colour of the drink are among the characteristics displayed by the plant. However, consumers are sometimes exposed to risks when the drink is consumed after 24 hours of preparation due to the proliferation of spoilage microorganisms in the drink. Most of these microbes thrive even at extreme temperatures. Unfortunately, some of these microorganisms are of public health importance causing diseases such as meningitis and dysentery. Researchers have revealed that roselle calyx is the major source of contamination in the drink. This paper reviews the suitability of the plant for soft drink production. It further highlights the nutrition, pharmacology, and limitations of the plant for soft drink production.